Optimization of the Physical and Mechanical Properties of Oriented Strandboard (Osb) From Low Quality of Timber in Environmental Sustainability - Yusfiandrita Rita; Nurhasan Syah (Science and Environmental Journal for Postgraduate, 2020)
Oriented Strandboard (OSB) is a product panel made of individual strands, bound with Phenol Formaldehyde (PF) and hot pressed at 170oC. In order to optimize the physical and mechanical properties of OSB, in order to obtain maximum benefits, steaming is used. From the sample test, the results of steaming time were considered significant on the physical and mechanical properties of OSB. The value of moisture content, thickness development and OSB water absorption are decreasing. The value of MOE, MOR, internal bond strength and screw holding increases. The optimal value is obtained at 2 hour steaming time, while the increase in thickness and water absorption, get maximum results at the measurement time of 8 hours. The physical and mechanical properties of OSB produced after going through the steaming process have met the particle board product standards (SNI 03-2105, 2006), JAS for Structural Plywood 1983 and JIS A Standard 5908: 2003 (Japanese Industrial Standards). Using, OSB is very appropriate to be used as a lightweight construction material and furniture as well as plywood, which will reduce the use of solid wood in nature for environmental sustainability.